2011
DOI: 10.1038/clpt.2011.108
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Pharmacokinetics of Oral Quinidine and Verapamil in Healthy Subjects: A Clinical Microdosing Study

Abstract: Microdosing studies are effective in enabling the early identification of the pharmacokinetic properties of compounds administered to humans. However, the nonlinearity of the pharmacokinetics between microdose and therapeutic dose, attributable to the saturation of metabolic enzymes and transporters, is a major concern. Verapamil and quinidine are good substrates of both the multidrug resistance 1 transporter (MDR1) and the cytochrome P450 (CYP) 3A4 enzyme (CYP3A4). We investigated their dose-dependent pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 22 publications
(26 reference statements)
5
38
0
Order By: Relevance
“…That verapamil elimination is dose dependent, with AUC VER ' increasing (Pang and Kwan, 1983); preformed norverapamil data are from Table 3. decreasing at higher dosing levels, confirmed nonlinearity in verapamil disposition, an observation that is in agreement with that inferred for the clinical pharmacokinetics of verapamil (Freedman et al, 1981;Shand et al, 1981;Anderson et al, 1982;Tartaglione et al, 1983;Toffoli et al, 1997;Maeda et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…That verapamil elimination is dose dependent, with AUC VER ' increasing (Pang and Kwan, 1983); preformed norverapamil data are from Table 3. decreasing at higher dosing levels, confirmed nonlinearity in verapamil disposition, an observation that is in agreement with that inferred for the clinical pharmacokinetics of verapamil (Freedman et al, 1981;Shand et al, 1981;Anderson et al, 1982;Tartaglione et al, 1983;Toffoli et al, 1997;Maeda et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…For quinidine, but not verapamil, the high-dose enterocyte concentration also exceeded the K m for CYP3A metabolism. These conclusions are consistent with clinical findings (Table 3) [36].…”
Section: Evaluation Of the Decision Tree With Selected Casessupporting
confidence: 93%
“…A recent review indicated that 27 of 35 (77 %) published cases comparing microdose and therapeutic dose pharmacokinetics displayed dose proportionality [12]. Importantly, these published cases include compounds that were specifically selected to address concerns about saturable processes that were raised a priori [2,[33][34][35][36]. It was suggested that such cases may be foreseeable by integrating the available preclinical data, but this had not yet been formally evaluated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lower availability was predicted with a microdose than with 40 mg, which corresponds to the clinical observation (Maeda et al, 2011). The simulated maximum concentration in the enterocytes was approximately 6.7 mM, which was smaller than the K m value of CYP3A4 (49.0 mM) and higher than the K m value for P-gp (0.622 mM).…”
Section: Discussionmentioning
confidence: 99%